Study on the effect of semisolid lubricants on tribological properties of hardened steel during boring process. (14th December 2020) - G., Lawrance; Paul, P. Sam; A.S., Varadarajan
Abstract : Purpose: In the internal turning process, tool life and work piece quality are greatly influenced by the generation of heat in the cutting zone. During machining, cutting fluids are applied at the cutting zones to reduce heat generation and enhance tribological properties. However, in the boring process, cutting fluids cannot be applied at cutting zone properly, and wastage of cutting fluid is a threat to the ecology and personnel health. Hence, application of semisolid lubricant in the boring process is considered as an innovative technique for temperature reduction in cutting zone because of its eco-friendly system, which also has a higher ability of biodegradability. This paper aims to study the influence of semisolid lubricants comprising of grease, graphite, aluminium oxide in different composition applied at a tool–chip, tool–work interface using a semisolid lubricant applicator applied with varying pressure. Design/methodology/approach: In the present study, the cutting performance during boring of AISI4340 steel is enhanced through the application of semisolid lubricant with different composition of grease, graphite and aluminium oxide applied at tool-work and tool-chip interface with varying pressure using semisolid lubricant applicator. Findings: The results show that use of semisolid lubricant like grease, graphite and nano aluminium oxide at tool-chip interface with maximum pressure reduces cutting temperature, tool vibration, cutting force and surface roughness. Originality/value: Reduce cutting temperature, tool vibration, cutting force and surface roughness.